The neurocognitive basis of borrowed context information. (June 2017) - O'Neill, Meagan; Diana, Rachel A.
Abstract: Falsely remembered items can be accompanied by episodic context retrieval. This finding is difficult to explain because there is no episode that binds the remembered item to the experimenter-controlled context features. The current study examines the neural correlates of false context retrieval when the context features can be traced to encoding episodes of semantically-similar items. Our neuroimaging results support a "dissociated source" mechanism for context borrowing in false memory. We found that parahippocampal cortex (PHc) activation, thought to indicate context retrieval, was greater during trials that involved context borrowing (an incorrect, but plausible source decision) than during baseline correct context retrieval. In contrast, hippocampal activation, thought to indicate retrieval of an episodic binding, was stronger during correct source retrieval than during context borrowing. Vivid context retrieval during false recollection experiences was also indicated by increased activation in visual perceptual regions for context borrowing as compared to other incorrect source judgments. The pattern of findings suggests that context borrowing can arise when unusually strong activation of a semantically-related item's contextual features drives relatively weak retrieval of the associated episodic binding with failure to confirm the item information within that binding. This dissociated source retrieval mechanism suggests that context-driven episodic retrieval does not necessarily lead to retrieval of specific item details. That is, source information can be retrieved in the absence of item memory.